Organizational Citizenship Behavior Ditinjau dari Organizational Justice dan Job Satisfaction - Ardana, Alin; Ekowati, Dian (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2022)
Anteraja is one of the express logistics companies, which already has of ± 400,000 branches throughout Indonesia. And has more than 500,000 packages in a day. The phenomenon raised in this study is about organizational citizenship behavior in Anteraja can be perceived by the level of organizational justice received by individual. This study aims to analyze the effect of organizational justice (distributive, procedural, and interactional) on organizational citizenship behavior by looking at the mediating role of job satisfaction. This study used a sample of 232 Anteraja employees in Jakarta Head Office. Statistical testing in this study using the help of software SmartPLS 3 version 3.2.9. The results in this study are quite interesting that one form of organizational justice, specifically distributive justice, has no significant effect on job satisfaction. In addition, it was also found that job satisfaction did not mediate the effect of distributive justice on organizational citizenship behavior.